The effect of a customised digital adherence tool on HIV treatment outcomes in young people living with HIV (YPLHIV) in Blantyre, Malawi: a protocol for a randomised controlled trial - Takondwa Charles Msosa; Iraseni Swai; Marion Sumari-de Boer; Kennedy Ngowi; Tobias F. Rinke de Wit; Rob Aarnoutse; Marriott Nliwasa (Trials, 2023)
Abstract Background People living with HIV (PLHIV) have to take lifelong antiretroviral treatment, which is often challenging. Young people living with HIV (YPLHIV) have the lowest viral load suppression rates in Malawi and globally, mostly due to poor treatment adherence. This is a result of complex interactions of multiple factors unique to this demographic group. The use of digital health interventions, such as real-time medication monitor (RTMM)-based digital adherence tools (DATs), could improve ART adherence in YPLHIV and subsequently improve viral load suppression which in turn could lead to reduced HIV-associated morbidity and mortality. Aim To provide the evidence base for a digital adherence intervention to improve treatment outcomes in YPLHIV on ART. Objectives 1. The primary objective is to determine the efficacy of a customised DAT compared to the standard of care in improving ART adherence in YPLHIV. 2. The secondary objective is to determine the efficacy of the customised DAT compared to the standard of care in improving viral load suppression in YPLHIV. Methodology This will be a parallel open-label randomised control controlled two-arm trial in which non-adherent YPLHIV in selected ART facilities in Blantyre will be randomised in a 1:1 ratio to a customised DAT and standard care arms and followed up for 9 months. The primary outcome is the proportion adherent at 9 months (> = 95% by pill count), and the secondary outcome is the proportion with viral load suppressed at 9 months (< 200 copies/ml). Discussion There is a paucity of good quality evidence on effective digital health interventions to improve ART adherence and viral load suppression in YPLHIV globally and particularly in HIV high-burden settings like Malawi. This study will provide good-quality evidence on the effectiveness of a customised DAT in improving ART adherence and viral load suppression in this important demographic. Trial registration The trial has been registered in the Pan African Clinical Trials Registry number: PACTR202303867267716 on 23 March 2023 and can be accessed through the following URL: https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=25424 . All items from the WHO Trial Registration Data Set are described in this manuscript.